IDENTIFIKASI TOPONIMI DESA DI KECAMATAN CILONGOK KABUPATEN BANYUMAS DALAM PERSPEKTIF KERUANGAN - Tommy Langgeng Abimanyu (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2018)
The location of Cilongok subdistrict, which is under Banyumas Regency, is quite far from the area of the spread of Sunda ethnic group. However, in Cilongok subdistrict there are names of villages that originated fromSundanese name, such as Cikidang, Cilongok, and Cipete. “Ci”, which means water or river, is a Sundanese generic name that becomes the characteristic of toponym. In addition, there are facts that indicate there were ethnic migrations. In a number of areasin West Java there are places that have the same names with that of in Banten. The purpose of this research is to describe characteristics of village toponyms in Sub Cilongok and to find out the factors that influence the characteristics. Using spatial approach, this qualitative research studied 20 villages located in Cilongok sub-district. The data were collected from library research, observations, interviews, and related documents.The data were examined using spatial pattern analysis. The results of this study indicate that the village toponyms in Cilongok sub-district were influenced by physico-natural, physico-artificial, and non physico-artificial phenomena. The village toponyms in Cilongok sub-district is the result of assimilation of Sundanese and Javanese cultures.